Different Classification Technique using Analysis of Student Academic Dataset - Umarani, N; Rajakumar, R (International Journal of Computer Sciences and Engineering, 2025)
Data mining methods are executed in numerous associations as a standard technique for breaking down the vast volume of accessible data, removing valuable data and information to help the real basic leadership forms. Data mining can be connected to wide assortment of utilizations in the instructive division to improve the execution of understudies and additionally the status of the instructive foundations. Instructive data mining is quickly creating as a key method in the examination of data produced in the instructive space. The point of this examination displays an investigation of each semester consequences of UG certificate understudies utilizing data mining strategy. This research work thinks about the outcome characterization algorithms. The correlation is finished utilizing the estimation of precision and estimations of Error Rate. This research work likewise demonstrates what algorithm is most reasonable for anticipating the execution of the understudies among the chose algorithms. The examination work is finished by considering different kinds of algorithm like choice tree algorithm, rule based algorithm, Bayesian algorithm and function based algorithms. This nonexclusive novel methodology can be reached out to different trains too